A Tool for Assessing Text Suitability for Greek Language Teaching. (December 2018) - Neofytou, Chrystalla; Hadzilacos, Thanasis
Viewing its use in language teaching mainly as a text corpus, this article examines the problem of the assessment of suitability of this material for use in the Greek language course in Cyprus schooling. The suitability of texts for use in language teaching is defined by four parameters, which are described in detail in this article: text readability, content, genre, and grammatical information. The literature review shows the research gap as to the ways of finding on the Web a suitable text for use in language teaching according to specific characteristics. The tool diaKeimenou, which is presented in this article, aims to fill this gap and help the teacher choose the most suitable texts for teaching with reasonable effort and time. The results of the usability evaluation of diaKeimenou are also presented in this article.